Microbiological Profile Resistant to Different Intracanal Medications in Primary Endodontic Infections - Ferreira, Nadia S. [UNESP]; Martinho, Frederico C. [UNESP]; Cardoso, Flavia G. R. [UNESP]; Nascimento, Gustavo G.; Carvalho, Claudio A. T. [UNESP]; Valera, Marcia C. [UNESP] (Elsevier B.V., 2015)
Introduction: This clinical study aimed to determine the microbiological profile resistant to different intracanal medications in primary endodontic infections by using both microbiological culture and the checkerboard DNA-DNA hybridization technique. Methods: Twenty primarily infected root canals were selected and then instrumented before being randomly divided into 2 groups according to the intracanal medications: calcium hydroxide (Ca[OH](2)) or Ca(OH)(2) + chlorhexidine (CHX). Samples were collected before and after root canal procedures, which consisted in submitting them to microbiological culture and processing them for checkerboard DNA-DNA hybridization. Results: No differences were found between the Ca(OH)(2) (99.98%) and Ca(OH)(2) + CHX groups (99.76%) regarding the median percentage values for the reduction of cultivable bacteria. The most frequently detected species were Capnocytophaga ochracea (70%) and Fusobacterium nucleatum ssp. vincentii (70%) in the initial samples. After instrumentation, the most frequently detected species were E. faecium (60%). After root canal treatments using either Ca(OH)(2) or Ca(OH)(2) + CHX as intracanal medications, the most frequently detected species were E nucleatum ssp. vincentii (90%) and Enterococcus faecium (40%), respectively. Both treatments significantly decreased the number of bacterial species compared with the initial sample. However, this reduction was significantly greater in the Ca(OH)(2) + CHX group (P < .05). This difference was also observed when evaluating the total bacterial load (P < .05). Conclusions: The use of Ca(OH)(2) associated with CHX as an intracanal medication showed better results by acting on gram-positive and gram-negative microorganisms although such an action to eradicate enterococci should also be sought.
Keywords: Bacteria; checkerboard DNA-DNA hybridization; endodontic infection